Internal abdominal hernia: Intestinal obstruction due to trans-mesenteric hernia containing transverse colon - Crispín-Trebejo, Brenda (2014)
INTRODUCTION Internal abdominal hernias are infrequent but an increasing cause of bowel obstruction still often underdiagnosed. Among adults its usual causes are congenital anomalies of intestinal rotation, postsurgical iatrogenic, trauma or infection diseases. PRESENTATION OF CASE We report the case of a 63-year-old woman with history of chronic constipation. The patient was hospitalized for two days with acute abdominal pain, abdominal distension and inability to eliminate flatus. The X-ray and abdominal computerized tomography scan (CT scan) showed signs of intestinal obstruction. Exploratory laparotomy performed revealed a trans-mesenteric hernia containing part of the transverse colon. The intestine was viable and resection was not necessary. Only the hernia was repaired. DISCUSSION Internal trans-mesenteric hernia constitutes a rare type of internal abdominal hernia, corresponding from 0.2 to 0.9% of bowel obstructions. This type carries a high risk of strangulation and even small hernias can be fatal. This complication is specially related to trans-mesenteric hernias as it tends to volvulize. Unfortunately, the clinical diagnosis is rather difficult. CONCLUSION Trans-mesenteric internal abdominal hernia may be asymptomatic for many years because of its nonspecific symptoms. The role of imaging test is relevant but still does not avoid the necessity of exploratory surgery when clinical features are uncertain.